2016
DOI: 10.1111/iep.12183
|View full text |Cite
|
Sign up to set email alerts
|

Acute paraquat exposure determines dose‐dependent oxidative injury of multiple organs and metabolic dysfunction in rats: impact on exercise tolerance

Abstract: This study investigated the pathological morphofunctional adaptations related to the imbalance of exercise tolerance triggered by paraquat (PQ) exposure in rats. The rats were randomized into four groups with eight animals each: (a) SAL (control): 0.5 ml of 0.9% NaCl solution; (b) PQ10: PQ 10 mg/kg; (c) PQ20: PQ 20 mg/kg; and (d) PQ30: PQ 30 mg/kg. Each group received a single injection of PQ. After 72 hours, the animals were subjected to an incremental aerobic running test until fatigue in order to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 50 publications
3
14
0
Order By: Relevance
“…The significantly higher AST, LDH, and ALT activities in the fish exposed to increasing atrazine across the treatment when compared with control groups could be as a result of leakage of aminotransferase (AT) enzymes from injured liver cells. These results were similar to that of Konstantinova & Russanov, (1999) who studied paraquat induced oxidative stress in rat liver. The increase in the value of the enzymes activity may be as a result of extra-cellular fluid as reported by Akanji, Olagoke, & Oloyede (1993) Both the AST and ALT are enzymes connected with liver parenchymal cells.…”
Section: Resultssupporting
confidence: 90%
“…The significantly higher AST, LDH, and ALT activities in the fish exposed to increasing atrazine across the treatment when compared with control groups could be as a result of leakage of aminotransferase (AT) enzymes from injured liver cells. These results were similar to that of Konstantinova & Russanov, (1999) who studied paraquat induced oxidative stress in rat liver. The increase in the value of the enzymes activity may be as a result of extra-cellular fluid as reported by Akanji, Olagoke, & Oloyede (1993) Both the AST and ALT are enzymes connected with liver parenchymal cells.…”
Section: Resultssupporting
confidence: 90%
“…Another interesting point observed in our study was that the groups that received only paracetamol presented a reduction in the number of these antioxidant enzymes. Similar to our findings, studies showed that during intense tissue oxidation, levels of antioxidant enzymes are often reduced due to the high levels of production and accumulation of O 2 induced by xenobiotics that increase enzyme consumption in intoxicated tissues [ 65 , 68 ]. In the analysis of glutathione S-transferase, the mice that received treatment with the extract of A. microcarpum + Paracetamol® showed an increase in the activity of these enzymes when compared to the group that received only paracetamol.…”
Section: Discussionsupporting
confidence: 89%
“…pseudoquina extract indicate their healing effects. These molecules are bioactive for the treatment of health disorders [ 7 , 43 ], with antioxidant [ 44 , 45 ] and regenerative [ 46 ] abilities, as reported for polyphenols of Dioclea violacea , Erythroxylum numularia [ 47 ], Brassica oleracea [ 48 ] and Bathysa cuspidata [ 31 ]. We believe that plant research is a promising tool for the discovery of extracts or bioactive molecules that can contribute to the treatment of various diseases.…”
Section: Discussionmentioning
confidence: 99%